Clinical Outcomes of Severe COVID-19 Patients Admitted to an Intermediate Respiratory Care Unit - Suarez-Cuartin, Guillermo; Gasa, Merce; Bermudo, Guadalupe; Ruiz, Yolanda; Hernandez-Argudo, Marta; Marin, Alfredo; Trias-Sabria, Pere; Cordoba, Ana; Cuevas, Ester; Sarasate, Mikel; Ariza, Albert; Sabater, Joan; et al. (Frontiers in Medicine, 2021)
Introduction: Many severe COVID-19 patients require respiratory support and monitoring. An intermediate respiratory care unit (IMCU) may be a valuable element for optimizing patient care and limited health-care resources management. We aim to assess the clinical outcomes of severe COVID-19 patients admitted to an IMCU. Methods: Observational, retrospective study including patients admitted to the IMCU due to COVID-19 pneumonia during the months of March and April 2020. Patients were stratified based on their requirement of transfer to the intensive care unit (ICU) and on survival status at the end of follow-up. A multivariable Cox proportional hazards method was used to assess risk factors associated with mortality. Results: A total of 253 patients were included. Of them, 68% were male and median age was 65 years (IQR 18 years). Ninety-two patients (36.4%) required ICU transfer. Patients transferred to the ICU had a higher mortality rate (44.6% Vs 24.2%; p<0.001). Multivariable proportional hazards model showed that age 65 years (HR 4.14; 95%CI 2.31-7.42; p<0.001); chronic respiratory conditions (HR 2.34; 95%CI 1.38-3.99; p=0.002) and chronic kidney disease (HR 2.96; 95%CI 1.61-5.43; p<0.001) were independently associated with mortality. High-dose systemic corticosteroids followed by progressive dose tapering showed a lower risk of death (HR 0.15; 95%CI 0.06-0.40; p<0.001). Conclusions: IMCU allow to safely and effectively manage severe COVID-19 patients requiring respiratory support and non-invasive monitoring, therefore reducing ICU burden. Older age and chronic respiratory or renal conditions are associated with worse clinical outcomes, while treatment with systemic corticosteroids may have a protective effect on mortality.